TINJAUAN YURIDIS TERHADAP PEMENUHAN HAK-HAK ANAK DI LEMBAGA PEMASYARAKATAN KLAS I A MAKASSAR - SULAIMAN, HERLINA (Lembaga Penelitian dan Pengabdian Masyarakat, 2017)
The perpetrator of the criminal act of the child cannot be equated with criminal adults. Therefore it needs more attention in the case of children. However, the child is the successor Nations that should be developed physically and mentally. The purpose of this research is to analyze the role of the Ombudsman in the performance of Marisa Polres versioned as well as analyze constraints are faced by Investigators in Marisa Polres versioned. This type of research is research used empirical research focus i.e. normative on secondary data sources (research libraries). This research uses the main data source i.e. secondary data, backed up with primary data sources. Secondary data is used that is derived from legislation such as the ACT on the criminal justice system of the child, the child protection ACT, Act No. 8 Of 1981 Year Book of the Police Act, Police ACT and some of the literature-literature as well as the results of his research,  and books related to the role of the Ombudsman in conducting versioned on criminal act committed by the child. Research results show that Marisa Polres in performing the investigation is a criminal act committed by the child by women and children protection Unit (UPPA). Starting from the stage of investigation, arrest, detention up at the stage of investigation conducted in accordance with the mandate of the ACT on the criminal justice system. Investigators in conducting versioned, get consideration from BAPAS. In addition, the investigators also act as mediator to conduct deliberations involving the child and the parent/guardian, the victim and the parent/guardian, supervisor of community, social professional pekera based on approach restorative. Obstacles faced by Investigators in the conduct of Marisa Polres diversion that is not yet the existence of BAPAS in counties Marisa so complicate investigators to coordinate-in terms of asking for consideration in doing versioned. In addition the party victims sometimes do not want to make peace so that the attempted diversion by Investigators was not achieved.